Utilization of water filtration ladders as science learning Media at cisarua 1 state elementary school - Mawardini, Annisa; Yektyastuti, Resti; Arina Putri; Nur Shabrina Khairunnisa; Siti Selvia Nurahma (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
Water is essential for human health and community welfare, but many students and teachers still do not understand how to process dirty water into clean water. This study aims to improve students' understanding of the concept of water filtration and raise awareness of the importance of environmental conservation through the application of water filtration media in learning. Researchers conducted observations and educational practices at SDN Cisarua 1 through the project activity of making water filtration ladders as a learning medium for fourth-grade students. The method of data collection through interviews and its implementation through several stages. The study was conducted on May 27, 2025, with 27 fourth grade students. In-depth interviews were conducted with 5 students. Based on the results of the study, 80% of students showed an increase in understanding. This can be proven through the results of interviews that revealed their understanding of how to use and the importance of water filtration. It can be concluded that learning using water filtration media has proven to be effective, this can be proven by the response and enthusiasm of students during the implementation.